The Matter of the Gods : Religion and the Roman Empire - Ando, Clifford, 1969- (Book collections on Project MUSE., 2009)
What did the Romans know about their gods? Why did they perform the rituals of their religion, & what motivated them to change those rituals? Clifford Ando explores the answers to these questions, pursuing a variety of themes essential to the study of religion in history.